Bird Diversity and its Potential for Tourism Activities in Mangrove Areas, Carocok Anau, West Sumatra, Indonesia - Khairini, Ridha; Mukhtar, Erizal; Novarino, Wilson (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Avitourism is activity that utilizes bird diversity in economic aspect that provides benefits for conservation and economic improvement. Mangrove ecosystem in Carocok Anau located in tourist area that has high potential to diversity of bird species. Data related to bird diversity and potential in tourism activities have not been conducted. This study aims to analyze bird diversity and its potential in tourism activities in Carocok Anau mangrove ecosystem area. This research was carried out from February until April 2024. The method used is the point count method. Data collection is species and numbers of bird species was carried out at 15 observation points. The distance of each points was 150 meters with 50 meters of radius observation. Data collection in 10 minutes of each point. Observation was conducted during four days, and continued by bird species identification. Data analysis used is Shannon Wiener diversity index, evenness index and richness index. The results found 40 bird species with 1023 individu. Dominated by family of E strildidae and species of Collocalia esculenta. The diversity index value of 2.51 included in medium diversity category. 0.68 for evenness index value with uneven category and 5.63 for richness index with high species richness category. Birds with ecotourism attractions found are three types of raptors, one endemic, 13 protected bird, there are eight bird with attractive feather colors and 20 bird with beautiful voices, so that the Carocok Anau mangrove ecosystem area has capability to avitourism activity.